Macroeconomic determinants of home financing in Malaysia : A comparative analysis of conventional and Islamic banks - Usman, Farrell Hazsan Emban (2014)
The purpose of this study is to analyze and compare the dynamic relationship between macroeconomic variables (i.e. gross domestic product, house prices, stock prices, and interest rate) and home financing provided by conventional and Islamic banks in Malaysia. The recent financial crisis has highlighted the importance of the interactions of macroeconomic factors and home financing. The dual banking system in Malaysia provides an important and distinct case study of the interplay of macroeconomic variables and home financing. The period covered for this study is from first quarter of 2007 to second quarter of 2014. This study employs time series analysis techniques such as autoregressive distributed lag (ARDL) bound-testing cointegration approach, impulse response function (IRF), and forecast error variance decomposition (FEVD) to analyze the long-run and short-run relationships among the variables. This study finds that macroeconomic variables have different long-run and short-run influence on home financing provided by conventional and Islamic banks. Both in the long-run and short-run, home financing provided by Islamic banks are more linked to real sector economy as compared to home financing provided by conventional banks. However, interest rate is found to have significant influence on both conventional and Islamic banks in the longrun. Based on the findings of this study, policy intervention to stimulate or dampen home financing provided by conventional banks must focus on influencing stock prices and monetary policy. On the other hand, policy intervention to stimulate or dampen home financing provided by Islamic banks must focus on GDP, house prices, and monetary policy